Entropy-Driven Amino Acid-Based Coacervates with Enzyme-Free Metabolism and Prebiotic Robustness - Shuai Cao (775058) (2025)
Protocells capable of nonenzymatic metabolism and environmental adaptation are essential models for understanding the emergence of cellular life. However, existing protocell designs often lack the robustness or prebiotic relevance to explain how functional supramolecular assemblies could have formed under early Earth conditions. In this study, we demonstrate that simple amino acid derivatives, observed on extraterrestrial bodies and under simulated prebiotic Earth conditions, undergo entropy-driven liquid–liquid phase separation to form membraneless protocells through a self-coacervation process. The synergistic effect of selective enrichment of metabolites and interfacial acceleration in these coacervate microdroplets enhances enzyme-free reactions, including sulfur metabolism and prebiotic pigment synthesis. The protocells are stabilized by water-mediated hydrogen-bonding networks and exhibit exceptional resilience to prebiotically plausible stressorssuch as high salinity (up to 4.0 M NaCl), high concentrations of divalent cations (4.0 M Mg2+/Ca2+), UV radiation, and extreme temperature fluctuationswhich typically disrupt existing vesicle-based systems. Remarkably, these structures autonomously generate and maintain a proton gradient (ΔpH ≈ 0.6–2.1) across their interfaces, enabling primitive chemiosmotic coupling via Na+–H+ antiport activity. They also adaptively remodel into compact spherical morphologies in response to sudden environmental changes, thereby preserving structural integrity. By integrating compartmentalization, nonenzymatic catalysis, energy transduction, and stress tolerance within a minimalist amino acid framework, our results establish a geochemically plausible pathway for the formation and persistence of functional protocells. This work highlights the potential of coacervate-based microcompartments to bridge nonliving and living systems by sustaining biochemical complexity under prebiotic conditions.